Quantification of the Elastic Moduli of Lumbar Erector Spinae and Multifidus Muscles Using Shear-Wave Ultrasound Elastography - Lim, Tae Hyun; Lee, Deukhee; Kim, Olga; Lee, Song Joo (Applied sciences, 2021)
Although spinal surgeries with minimal incisions and a minimal amount of X-ray exposure (MIMA) mostly occur in a prone posture on a Wilson table, the prone posture’s effects on spinal muscles have not been investigated. Thus, this study used ultrasound shear-wave elastography (SWE) to compare the material properties of the erector spinae and multifidus muscles when subjects lay on the Wilson table used for spinal surgery and the flat table as a control condition. Thirteen male subjects participated in the study. Using ultrasound SWE, the shear elastic moduli (SEM) of the erector spinae and multifidus muscles were investigated. Significant increases were found in the SEM of erector spinae muscle 1, erector spinae muscle 2, and multifidus muscles on the Wilson table (W) compared to in the flat table (F; W:22.19 ± 7.15 kPa, F:10.40 ± 3.20 kPa, p < 0.001; W:12.10 ± 3.31 kPa, F: 7.17 ± 1.71 kPa, p < 0.001; W: 18.39 ± 4.80 kPa, F: 11.43 ± 2.81 kPa, p < 0.001, respectively). Our results indicate that muscle material properties measured by SWE can be changed due to table posture, which should be considered in biomechanical modeling by guiding surgical planning to develop minimal-incision surgical procedures.